Public ritual apology – A case study of Chinese. (December 2018) - Kadar, Daniel Z.; Ning, Puyu; Ran, Yongping
Abstract: The present paper explores the phenomenon of 'public ritual apology'. In our definition, this phenomenon covers an apology performed in front of public, and which is ritual in the sense that it is symbolic and expected to restore the moral order of the public, rather than grant actual reconciliation between the apologiser and the offended party. Thus, 'public ritual apology' usually occurs in contexts when someone apologises for acts that are deemed as grave and in the case of which apology is seemingly dysfunctional in the sense that it cannot usually grant forgiveness. Public ritual apology is a regretfully neglected area, in spite of the fact that such apologies are not only frequent but also generate significant public attention in media – thus, this paper fills an important knowledge gap. In our paper we focus on Chinese public ritual apologies, which are noteworthy to explore as Chinese is stereotypically referred to as a culture which disprefers apologising behaviour. Our methodology is predominantly interactional and metapragmatic, and it combines qualitative research with quantitative elements.